Barriers and enablers to meaningful youth participation in mental health research: qualitative interviews with youth mental health researchers. (2nd January 2019) - Faithfull, Sarah; Brophy, Lisa; Pennell, Kerryn; Simmons, Magenta B.
Abstract: Background: Involving young people in co-designing and conducting youth mental health research is essential to ensure research is relevant and responsive to the needs of young people. Despite this, many barriers exist to meaningful involvement. Aims: To explore the experiences, barriers and enablers to partnering with young people for mental health research. Methods: Semi-structured, qualitative interviews were conducted with 19 researchers employed at a youth mental health research institute in Australia. Thematic analysis was used to analyse these data. Results: How researchers conceptualise youth participation was related to how confident and competent they felt engaging with young people. Attitudes and beliefs about the impact of youth participation on research quality were related to emotional factors, such as feelings of anxiety or excitement. Whether researchers engaged in youth participation was affected by resources, culture and the structures that their organisation had in place. Conclusion: Researchers generally want to engage young people in their work, but several factors can hinder this. By understanding the challenges facing researchers, and drawing on the factors that encourage and support those already engaging with young people, a framework to support genuine and meaningful youth participation in mental health research can be developed.